Downsizing and surviving employees' engagement and strain: The role of job resources and job demands - Katja Dlouhy; Anne Casper (Human Resource Management, 2021)
Downsizing is widely assumed to detrimentally affect surviving employees' engagement and health through increased demands and decreased resources. Building on job demands–resources theory, we assess whether these effects occur and whether job demands and resources moderate the detrimental effects of downsizing on employee health and engagement. We conceptualize downsizing as a stressor event, and we explain its relationship with employee health through the job demands work overload and job insecurity are (two) job demands, as well as its relationship with employee engagement through the job resources supervisor support and opportunities for development are job resources. Using data from two large representative samples of German employees, we show that job demands mediate the negative relationship between downsizing and employees' psychological and physical health and that job resources mediate the negative relationship between downsizing and engagement. We find little support for the assumption that job resources alleviate the indirect effects of downsizing on surviving employees' health, or that job demands strengthen the indirect effects of downsizing on surviving employees' engagement. We discuss how these findings expand our understanding of downsizing and outline practical implications for human resource practitioners.
Keywords: 650; downsizing; employee engagement; physical health; psychological health